Efficacy of corticosteroids as an adjunctive therapy in the treatment of community-acquired pneumonia: a systematic review and meta-analysis - Lydia Mukanhaire; Huijie Li; Zhengyue Fan; Liping Yang; Yuxuan Zheng; Zhuoling Ran; Xiaoyu Zong; Lingjian Zhang; Yang Gong; Changqing Yang; Jian Gong (Compuscript Ltd, 2023)
The objective of this study was to systematically evaluate the clinical efficacy of the complementary use of corticosteroids in the treatment of community-acquired pneumonia (CAP). We searched all relevant documents in five scientific databases from inception to June 2022 to collect clinical trials (randomized controlled trials and controlled trials) reporting on the adjunctive use of corticosteroids in CAP treatment. The primary outcome was mortality, and secondary outcomes included the time to clinical stability, therapeutic efficacy, duration of antibiotic treatment and length of hospital/ICU stay. Therapeutic efficacy was defined as the rate of achieving clinical recovery with no fever, improvement or disappearance of cough. Clinical stability was defined by improvements in laboratory values. Two researchers independently screened the literature according to the inclusion and exclusion criteria, extracted data and evaluated the quality of literature. Statistical analysis and meta-analysis of intervention measures and indicators were performed with IBM SPSS and RevMan 5.4 software. Nine randomized controlled trials comprising 2673 participants with CAP (1335 in the corticosteroid group and 1338 in the control group) were identified and included in this study. The mean cumulative corticosteroid dose and treatment duration were 298.00±287.140 mg and 5.22±1.787 days, respectively. Corticosteroid treatment was not associated with a significant decrease in mortality (RR; 95% CI, 0.96 [0.67-1.38], P=0.83). Because of the low number of included patients in our study, more studies with larger sample sizes and high-quality randomized, double-blind controlled trials are needed to confirm the results.